EFEKTIVITAS LAYANAN INFORMASI MENGGUNAKAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KETERAMPILAN BERTANYA SISWA - Ilham Khairi Siregar (Program Studi Bimbingan dan Konseling FKIP UMSU, 2018)
The purpose of this study on the effectiveness of the service information using scientific approach and use the lecture method to improve the skills of the students asked. The research is a Quasi Experiment with a design pretest-posttest control group design. The study population is students of Madrasah Aliyah Aisiyah Binjai and SMA Muhammadiyah Binjai, subjects were selected using purposive sampling technique. The research instrument uses a questionnaire. Data were analyzed using the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Independent Samples with SPSS version 20.0. Based on the findings, the scientific information services with more effective approach to improve students' skills in asking questions.